Natural disasters and governmental aid: Is there a charity hazard? - Mark Andor; Daniel Osberghaus; Michael Simora (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
In the aftermath of natural disasters, governments frequently provide financial aid for affected households. This policy can have adverse effects if individuals anticipate it and forgo private precaution measures. While theoretical literature unequivocally suggests this so called "charity hazard", empirical studies yield ambiguous results. Drawing on rich survey data from German homeowners, we analyze charity hazard for different flood precaution strategies, namely insurance uptake and non-financial protection measures, and different flood risk areas. Our results indicate a substantial charity hazard in the insurance market for individuals residing in flood-prone areas. In contrast, we find a positive correlation between governmental aid and non-financial protection measures. Moreover, our results suggest that insurance and non-financial protection measures are rather complements than substitutes. Finally, we provide suggestive evidence that status-quo bias might play an important role for insurance uptake.
urn:nbn:de:bsz:180-madoc-438784
Keywords: Q54; C35; R22; 330; Adaptation; Flood Protection; Flood Insurance; Objective Flood Risk; Charity Hazard